Pendampingan Drone Mapping Untuk Membantu Mitigasi Bahaya Banjir Rob di Kawasan Pesisir Kabupaten Tegal, Jawa Tengah - Saputra, Aditya; Danardono, Danardono; Wibowo, Afif Ari; Surachman, Dedi; Altair, Garin Rachmad; Al-Ghowazi, Sholakhuddin Akhmad; Natsir, Muhammad (Universitas Muhammadiyah Surakarta, 2024)
The phenomenon of tidal flood in the northern coastal areas of Java Island, which frequently occurs nowadays, is likely a consequence of rising sea levels due to global warming. The phenomena of urbanization and industrialization in the northern coastal areas of Tegal Regency can also contribute to the increase in built-up areas, adding pressure to the land surface in the coastal regions. Additionally, intensive groundwater extraction is occurring in densely populated coastal areas due to various activities. The high concentration of industrial and residential zones along the coast of Tegal Regency, coupled with extensive land subsidence due to intensive water abstraction, can lead to subsidence phenomena. The combination of rising sea levels and land subsidence can exacerbate the impact of tidal floods, making them more widespread and severe. The coastal areas of Tegal Regency are among those frequently affected by tidal floods. Analyzing tidal floods is crucial for integrated coastal management to support regional development. Assistance in developing a tidal flood mitigation plan in this coastal area is instrumental for local governments in planning and spatial arrangement in Tegal Regency. Support has been provided to local authorities, including BAPPEDA and Litbang Tegal Regency, to plan spatial arrangements in the northern coastal areas of Tegal Regency. The assistance activities include drone photography in the most severely affected areas, such as Kramat District. Additionally, the team periodically measures elevation to help local governments identify the potential occurrence of land subsidence. Furthermore, a Forum Group Discussion has been conducted to formulate the most suitable mitigation plan considering the conditions in Tegal Regency.